Single sequence repeat markers associated with partial resistance in sunflower to Phoma macdonaldii - DAVAR, Robab; DARVISHZADEH, Reza; KHOLGHI, Maryam; REZAEE DANESH, Younes; AZIZI, Majid; SHAH, Denis (Phytopathologia Mediterranea, 2012)
Phoma black stem of sunflower, caused by Phoma macdonaldii, occurs in many countries. The objective of the present study was to estimate the number of markers and genomic regions in sunflower associating with Phoma black stem resistance. Genetic variability among 32 sunflower genotypes, including recombinant inbred lines and their parents, M7 mutant lines developed by gamma irradiation, and some genotypes from different countries of origin, was evaluated using simple sequence repeat (SSR) markers. Eighty-eight markers were generated at 38 SSR loci, with a mean number of alleles per locus of 2.32. Using susceptibility data of 32 sunflower genotypes against seven P. macdonaldii isolates (Darvishzadeh et al., 2007), one to four markers were associated with each of seven different P. macdonaldii isolates. To reduce the probability of false positives, a sequential Bonferroni-experiment-wise P-value was used for each marker trait association tested. The identified markers showed a promising trend, although they did not pass the more stringent bar of statistical significance, and should be studied further.